The Impact of Ecoregional Mobilization on Mountain Policies in the Swiss Alps and California’s Sierra Nevada - Jörg Balsiger (Revue de Géographie Alpine)
Mountain regions have occupied a significant role in the political evolution, economic history, and sociocultural imaginary of Switzerland and California, yet the emergence of the modern state and the global economy have meant their increasing marginalization. During the last four decades, both polities have devised targeted strategies, policies, and programs for mountain regions. This article suggests that ecoregional mobilization has played a significant role in shaping the nature and evolution of these policies. Expanding and specifying arguments found in the policy networks literature, it argues that changes in the nature of dynamics of ‘organizational landscapes’ (the assemblage of state and non-state actors sharing a common concern for a policy issue or set of issues) precipitate transformations in ‘policy architectures (the structure and substantive orientation of public policy goals and instruments). Applying this framework to developments in the Swiss Alps and California’s Sierra Nevada during the last forty years, the article explains how ecoregional mobilization shaped opposite trends in the mountain areas, namely a shift form infrastructure development to nature conservation in the Alps, and a shift from nature conservation to local economic development in the Sierra Nevada.